Effect of hexamethylenetetramines (HMT) surfactant concentration on the performance of TiO2 nanostructure photoelectrochemical cells - Rahman M.Y.A.; Umar A.A.; Roza L.; Salleh M.M. (Maik Nauka Publishing / Springer SBM, 2023)
Hexamethylenetetramine (HMT) surfactant was used to modify the morphology of TiO2 thin film nanostructure prepared by a simple technique, namely, liquid phase deposition (LPD) during its growth process. In order to obtain various surface morphologies of TiO2 nanostructures, the concentration of HMT was varied from 10 to 100 mM. It was found that with an increase in concentration of HMT, the morphology of TiO2 nanorod in term of its grain size decreases due to the particles agglomeration grown on the surface. The TiO2 nanostructures with various grain sizes were utilized as photovoltaic materials in photoelectrochemical cell measurement. The highest performance of the cell in terms of the short-circuit current density, Jsc was 0.069 mA cm?2. This result was achieved from the TiO2 nanorod cell with the smallest grain size, 12 ± 2 nm. The Jsc of the cell increased with concentration of HMT. The cell utilizing the TiO2 nanostructure with the smallest grain size possessed the best interfacial contact at the TiO2/electrolyte containing iodide/triiodide redox couple. Thus, the redox reaction was optimised at this interface. © 2014, Pleiades Publishing, Ltd.